Memory impairment caused by cerebral hematoma in the left medial temporal lobe due to ruptured posterior cerebral artery aneurysm - Maeshima, Shinichiro (BioMed Central, 2014)
BACKGROUND: Cognitive disorders, such as memory disturbances, are often observed following a subarachnoid hemorrhage. We present a very rare case where rupture of a posterior cerebral artery aneurysm caused restricted damage to the hippocampus unilaterally, and caused memory disturbances. CASE PRESENTATION: A 56-year-old, right-handed man, with a formal education history of 16 years and company employees was admitted to our hospital because of a consciousness disturbance. He was diagnosed as having a subarachnoid hemorrhage due to a left posterior cerebral artery dissecting aneurysm, and coil embolization was performed. Subsequently, he had neither motor paresis nor sensory disturbances, but he showed disorientation, and both retrograde and anterograde amnesia. Although immediate recall and remote memory were almost intact, his recent memory was moderately impaired. Both verbal and non-verbal memories were impaired. Brain computed tomography (CT) and magnetic resonance imaging (MRI) revealed a cerebral hematoma in the left temporal lobe involving the hippocampus and parahippocampal gyrus, and single-photon emission computed tomography (SPECT) demonstrated low perfusion areas in the left medial temporal lobe. CONCLUSIONS: We suggest that the memory impairment was caused by local tissue destruction of Papez’s circuit in the dominant hemisphere due to the cerebral hematoma.